nStock: notified stocks management system for food and beverages industry / Azmi Abu Seman ... [et al.] - Abu Seman, Azmi; Abdul Wahab, Nufael; Ibrahim, Norfiza; Abdul Wahab, Nadia (Universiti Teknologi MARA, Perlis, 2024)
The development of a web-based stock management system aims to provide effective control over sales and stock levels for the food and beverage industry. The web-based application provides a platform for staff members and business proprietors to effectively modify and manage data related to stock and transactions. However, it is apparent that bakery enterprises exhibit a shared approach in their stock management procedures. The baker has a responsibility to manually update the stock availability on the WhatsApp group following each production. In order to maintain continuous production, it is imperative for management to take proactive measures by initiating the procurement of fresh stock from the vendor when the existing stock nears depletion. One potential resolution is the implementation of a streamlined stock management system that effectively addresses the needs of both bakers and managers. The objective of this project is to meet the demand for effective stock management among bakery store owners by offering a user-friendly and dependable system. The nStock system has been intentionally developed with the objective of effectively overseeing the procurement of raw materials from suppliers and accurately tracking the stock allocated for bakery production. The solution aims to employ Telegram bot services as a mechanism for alerting the management in the event that the stock levels fall below the predetermined reorder threshold. The approach employed by the project is in accordance with the Waterfall Model of System Development Life Cycle (SDLC). A functionality test is conducted prior to implementation in order to verify its compliance with the specified design and functional requirements. Notably, each participant provided the system with a "pass" rating, indicating its successful functioning and meeting their expectations.